Giving A Warm Compress To Overcome Back Pain In Pregnant Women - Kharisma Virgian; Nurul Komariah; Asri Noviyanti (CV. AFDIFAL MAJU BERKAH, 2025)
Back pain is one of the most common discomforts, during pregnancy many pregnant women experience back pain. Back pain is the most common complaint with a prevalence rate of 49%. However, about 80-90% of those who experience back pain say that they do not make any effort to overcome the onset of these symptoms, in other words only about 10-20% of those who seek medical care from health care workers. The purpose of this Community Service is to empower pregnant women in doing warm compresses. This Community Service activity was carried out on 20 pregnant women in the Sukajadi Health Center Area, Talang Kelapa District. First, a pre-test was carried out using VAS to measure pain and explained how to do a warm compress, monev was carried out through WA group by being given a warm compress video and then given a VAS questionnaire. Results The mother seemed enthusiastic in participating in the service activities, actively asking questions related to complaints during pregnancy. The result was pain, which was 25% mild pain and 75% moderate pain. While in Wa Group, mothers are active in responding and learning videos. The results were 75% mild pain and 25% moderate pain. Mommy understands and understands how to do a warm compress on the back area. The mother's pain is reduced.